2014
DOI: 10.1111/aor.12310
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐Engineered Tracheal Reconstruction Using Three‐Dimensionally Printed Artificial Tracheal Graft: Preliminary Report

Abstract: Three-dimensional printing has come into the spotlight in the realm of tissue engineering. We intended to evaluate the plausibility of 3D-printed (3DP) scaffold coated with mesenchymal stem cells (MSCs) seeded in fibrin for the repair of partial tracheal defects. MSCs from rabbit bone marrow were expanded and cultured. A halfpipe-shaped 3DP polycaprolactone scaffold was coated with the MSCs seeded in fibrin. The half-pipe tracheal graft was implanted on a 10 × 10-mm artificial tracheal defect in four rabbits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 39 publications
1
121
0
2
Order By: Relevance
“…Beyond epithelial grafting, 3D-printing has been used in the production of related structures, such as the trachea itself. Mesenchymal stem cells have been used with 3D-printed PCL scaffolds to create implantable structures which 14 maintain the luminal shape and function of the trachea in rabbits 43 . Furthermore, in vitro work on the development of a 3D-printed tissue-engineered trachea has demonstrated a dramatic capacity for regeneration and realistic mechanical qualities 44 .…”
Section: Grafting Prostheses and Reconstructionmentioning
confidence: 99%
“…Beyond epithelial grafting, 3D-printing has been used in the production of related structures, such as the trachea itself. Mesenchymal stem cells have been used with 3D-printed PCL scaffolds to create implantable structures which 14 maintain the luminal shape and function of the trachea in rabbits 43 . Furthermore, in vitro work on the development of a 3D-printed tissue-engineered trachea has demonstrated a dramatic capacity for regeneration and realistic mechanical qualities 44 .…”
Section: Grafting Prostheses and Reconstructionmentioning
confidence: 99%
“…The printed trachea Vivekkumar Patel, Bryan M. Burt long term engraftment and vascularization (5)(6)(7).…”
Section: Editorialmentioning
confidence: 99%
“…First, the authors show that PCL, a popular biodegradable synthetic material that may be customized to size and shape by 3D fusion deposition printing, is a compatible substrate for human mesenchymal stem cell (hMSC) growth in vitro, and therefore would allow for cell growth and good engraftment with host tissue (4,5). Next, the authors demonstrate that preoperative CT scanning may be used to generate customized 3D printed PCL C-rings to attach to the dermal collagen matrix for implantation as a composite tracheal graft.…”
mentioning
confidence: 99%
“…Firstly, to produce the medical models and external medical instruments by biological incompatibility and non-degradable materials; Secondly, to produce permanent implants by biocompatible and non-degradable materials; Thirdly, to produce tissue engineering support by biocompatible and degradable materials; Fourthly, to produce manual biological organ or tissues by living cells, proteins, and other extracellular materials [11][12][13][14][15][16]. These four levels in solving airway-related problems will be introduced respectively as follows.…”
Section: The Role That 3d Bio-printing Plays In Medical Revolutionmentioning
confidence: 99%
“…Chang, et al used polycaprolactone (PCL) to print the patch of rabbit tracheal damage. Postoperative tissue compatibility and repair effect experiments confirmed that the 3D printing patch repaired airway function effectively [11]. Tam, et al printed a tracheobronchial tree for a patient with recurrent polychondritis to guide subsequent tracheostomy or tracheal stent placement [32].…”
Section: Anesthesiology: Although Some Clinical Randomizedmentioning
confidence: 99%